PENGARUH MEDIA DIORAMA TERHADAP PEMAHAMAN PESERTA DIDIK KELAS V di SDN NANGKA KUNINGAN JAWA BARAT - Hilda Nova Aprilia, Hilda Nova Aprilia (Jurnal PGSD, 2024)
Abstract Based on research, it is known that the level of understanding of class V students at Nangka State Elementary School is low due to the minimal use of relevant learning media. So the aim of the research is to determine the effect of diorama media on students' understanding of class V science lessons at Nangka State Elementary School. The method used in this research was Pre-Experimental Design with One Group Pretest-Posttest design carried out by SD Negeri Nangka. The population in this study were all fifth grade students at SD Negeri Nangka, even semester of the 2023/2024 academic year. The sample in this research was class V, totaling 20 people as the experimental class. The data collection used is test questions in the form of essays. The research results showed that there was an increase in students' understanding seen from the average posttest score, namely 79.80, while the average pretest score was only 46.50. The results of the Paired Sample T-Test which was used to determine the test results of differences in students' understanding abilities obtained a Sig (2-tailed) result of 0.000 < 0.05. So Ha is accepted and Ho is rejected, which means there is a significant influence on students' understanding abilities. Keywords: Media Diorma, Student Understanding.